Gender inclination in English and Arabic teaching professions - Kama, Nonglaksana; Mat Daud, Nuraihan; Mat Daud, Nor Shidrah (IDOSI Publications, 2014)
Gender stereotyping in society may influence career aspirations. This research seeks to determine if this is true for language teaching profession. The study focuses on the distribution of English and Arabic teachers according to their gender. For this purpose, the number of English and Arabic instructors or academic staff at the public universities in Malaysia was surveyed. The results were compared and the study revealed that there was a higher number of female English instructors/academic than Arabic. On the other hand, males generally outnumbered females in the area of Arabic language teaching. Some possible explanations for the findings are discussed. Key words: Arabic Teacher English Teacher Gender Stereotyping